Partial unilateral lentiginosis: a clinicopathological analysis of 32 cases on the head and neck area in Korea. (21st May 2021) - Kim, Hak Tae; Choi, Myoung Eun; Na, Hyoungmin; Lee, Woo Jin; Won, Chong Hyun; Lee, Mi Woo; Choi, Jee Ho; Chang, Sung Eun
Abstract: Background: Partial unilateral lentiginosis (PUL) is a rare acquired circumscribed hyperpigmentation characterized by multiple simple lentigines involving half of the body. Since the previous studies of PUL were mostly based on case reports and the current literature lacks well‐designed retrospective studies that involve a large number of cases, PUL is not a well‐defined entity, and differential diagnosis with nevus spilus is still difficult. This study aims to evaluate clinical and histopathological characteristics and treatment outcomes of PUL on head and neck area of Koreans. Methods: Thirty‐two patients with PUL on head and neck area were diagnosed clinicohistopathologically at the Asan Medical Center from 2004 to 2017. Their medical records, photographs, and biopsy specimens were reviewed, and immunohistochemical staining for protein kinase C (PKC)‐βΙΙ was evaluated for melanogenic activity. Results: Four patients (12.5%) of PUL had congenital lesions, and 24 (75.0%) had age of onset younger than 10 years. Confluency of lentiginous lesions (100%) and mild to moderate background interlesional hyperpigmentation (90.6%) were observed. The lentiginous lesions showed increased melanocytes, melanophages, basal melanins, lentiginous hyperplasia, and perivascular inflammatory cells compared with background interlesional hyperpigmentation, and PKC‐βΙΙ was focally positive in 7 of 12 stained PUL lesions. Among the 16 patients who received laser treatments, 10 (62.5%) showed more than 50% of improvement. Conclusions: The findings of this study will allow for improved diagnosis of PUL and understanding of its features, which may facilitate proper management in the future.